In the shadow of the oaks. Romantic memory and intertextual strategy in the prologue to “A Life” - Matteo Rosario Maria Branduardi (Finzioni, 2022)
Through a new analysis of the letter that opens Svevo’s first novel, Una vita, addressed by the protagonist Alfonso Nitti to his mother, this article aims to investigate the subterranean intertextual strategy adopted by the author to provide an initial psychological portrait of his character, surfacing in transparency behind the official presentation entrusted to Alfonso’s voice. In particular, the analysis of a short narrative segment generally traced by critics to a distant bucolic-Virgilian influence, reveals the closest and most significant presence, behind the prologue of Una vita, of Romantic literature, and specifically of Goethe’s Werther, a model revisited problematically by Svevo and assumed in the terms not of an inert acquiescence, but of a manifest impossibility of recovery.